A Case of Disseminated Histoplasmosis Detected in Peripheral Blood Smear Staining Revealing AIDS at Terminal Phase in a Female Patient from Cameroon - Christine Mandengue Ebenye (Case Reports in Medicine)
Histoplasmosis is endemic in the American continent and also in Sub-Saharan Africa, coexisting with the African histoplasmosis. Immunosuppressed patients, especially those with advanced HIV infection develop a severe disseminated histoplasmosis with fatal prognosis. The definitive diagnosis of disseminated histoplasmosis is based on the detection of Histoplasma capsulatum from patient’ tissues samples or body fluids. Among the diagnostic tests peripheral blood smear staining is not commonly used. Nonetheless a few publications reveal that Histoplasma capsulatum has been discovered by chance using this method in HIV infected patients with chronic fever and hence revealed AIDS at the terminal phase. We report a new case detected in a Cameroonian woman without any previous history of HIV infection. Peripheral blood smear staining should be commonly used for the diagnosis of disseminated histoplasmosis in the Sub-Saharan Africa, where facilities for mycology laboratories are unavailable.